42nd AIAA Aerospace Sciences Meeting and Exhibit 2004
DOI: 10.2514/6.2004-154
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Plasma Expansion Using a Two-Timescale Accelerated Particle-In-Cell Method

Abstract: Public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing this collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden to Department of Defense, Washington Headquarters Services, Directorate for Info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Gibbons et al 3 also demonstrated the subcycling technique in which the slower moving neutrals are propagated at a larger time step than the faster moving ions. Gibbons et al 4 demonstrated the use of the subcycling scheme with a scheme that decoupled the modeling of surface interactions from the plume propagation. It utilizes particle sources from the surfaces in place of the self-consistent surface interaction modeling.…”
Section: Nomenclaturementioning
confidence: 99%
“…Gibbons et al 3 also demonstrated the subcycling technique in which the slower moving neutrals are propagated at a larger time step than the faster moving ions. Gibbons et al 4 demonstrated the use of the subcycling scheme with a scheme that decoupled the modeling of surface interactions from the plume propagation. It utilizes particle sources from the surfaces in place of the self-consistent surface interaction modeling.…”
Section: Nomenclaturementioning
confidence: 99%